(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Ensuring customer satisfaction is the key to a successful retail business. The process of attracting new customers always involves more money, time and energy. In order for a company to retain existing customers and build relationships with them, one of the basic tasks is to know the factors and levels that affect their satisfaction. In the current situation of COVI-19, this poses even greater obstacles and challenges. In order to identify the company's ability to ensure competitiveness in a crisis situation, the authors have set the goal of the research to study the factors influencing retail consumer behavior under COVID-19 circumstances. This study will provide retail businesses with an understanding of the need for consumer relationship management in a restricted situation. From the scientific point of view, the authors have analyzed the theoretical aspects and summarized the approach to the understanding of buyers' behavior in crisis conditions. As a result of the research, the authors conclude that even in crisis situations, companies can manage the relationship with consumers and shape the attitude of buyers, which can be one of the tools for ensuring competitiveness.